Wnt Signaling Coordinates the Expression of Limb Patterning Genes During Axolotl Forelimb Development and Regeneration - Lovely, Alexander M.; Duerr, Timothy J.; Qiu, Qingchao; Galvan, Santiago; Voss, S. Randal; Monaghan, James R. (Frontiers in Cell and Developmental Biology, 2022)
After amputation, axolotl salamanders can regenerate their limbs, but the degree to which limb regeneration recapitulates limb development remains unclear. One limitation in answering this question is our lack of knowledge about salamander limb development. Here, we address this question by studying expression patterns of genes important for limb patterning during axolotl salamander limb development and regeneration. We focus on the Wnt signaling pathway because it regulates multiple functions during tetrapod limb development, including limb bud initiation, outgrowth, patterning, and skeletal differentiation. We use fluorescence in situ hybridization to show the expression of Wnt ligands, Wnt receptors, and limb patterning genes in developing and regenerating limbs. Inhibition of Wnt ligand secretion permanently blocks limb bud outgrowth when treated early in limb development. Inhibiting Wnt signaling during limb outgrowth decreases the expression of critical signaling genes, including Fgf10, Fgf8, and Shh, leading to the reduced outgrowth of the limb. Patterns of gene expression are similar between developing and regenerating limbs. Inhibition of Wnt signaling during regeneration impacted patterning gene expression similarly. Overall, our findings suggest that limb development and regeneration utilize Wnt signaling similarly. It also provides new insights into the interaction of Wnt signaling with other signaling pathways during salamander limb development and regeneration.